2018
DOI: 10.3390/rs10040544
|View full text |Cite
|
Sign up to set email alerts
|

Towards Operational Monitoring of Forest Canopy Disturbance in Evergreen Rain Forests: A Test Case in Continental Southeast Asia

Abstract: This study presents an approach to forest canopy disturbance monitoring in evergreen forests in continental Southeast Asia, based on temporal differences of a modified normalized burn ratio (NBR) vegetation index. We generate NBR values from each available Landsat 8 scene of a given period. A step of 'self-referencing' normalizes the NBR values, largely eliminating illumination/topography effects, thus maximizing inter-comparability. We then create yearly composites of these self-referenced NBR (rNBR) values, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 53 publications
1
42
0
Order By: Relevance
“…Against this background, this study has two main objectives: (1) The mapping of forest disturbances caused by selective logging in seven sites under sustainable forest management (SFM) within the Brazilian State of Amazonas and (2) the comparison of the effectiveness of Landsat 8 data versus Sentinel-2 imagery for such purpose. To accomplish these objectives, we applied the "∆rNBR approach"-a modification of the normalized burn ratio (NBR) index-which has successfully been used to map forest disturbances in (semi-)evergreen forests in continental Southeast Asia [50]. Instead of working with single satellite scenes, this approach uses a time series analysis of all available satellite images and calculates the changes between two periods.…”
Section: Introductionmentioning
confidence: 99%
“…Against this background, this study has two main objectives: (1) The mapping of forest disturbances caused by selective logging in seven sites under sustainable forest management (SFM) within the Brazilian State of Amazonas and (2) the comparison of the effectiveness of Landsat 8 data versus Sentinel-2 imagery for such purpose. To accomplish these objectives, we applied the "∆rNBR approach"-a modification of the normalized burn ratio (NBR) index-which has successfully been used to map forest disturbances in (semi-)evergreen forests in continental Southeast Asia [50]. Instead of working with single satellite scenes, this approach uses a time series analysis of all available satellite images and calculates the changes between two periods.…”
Section: Introductionmentioning
confidence: 99%
“…Passive optical remote sensing assessments at resolutions as fine as 20-30 m have been used to classify logged forests with moderate accuracy. However, they have struggled to quantify the extent, intensity, and duration of logging damage because of the lack of regular cloud-free repeat observations and because rapid canopy regeneration masks logging effects after as few as three years [25][26][27]. Moreover, a 30 m spatial resolution is not sufficient to resolve mortality of a single canopy tree [28].…”
Section: Introductionmentioning
confidence: 99%
“…Landsat TOA reflectance-based EVI values were generally higher than surface reflectance (SR) based values [78] and therefore TOA data showed greater potential to provide accurate phenology-based classification [53,79,84,85]. Several studies have successfully applied TOA data for mapping the paddy rice [63,78,79,86,87] and mapping the vegetation distribution [17,22,53,84,88] using phenology-based methods. These studies have suggested that TOA data can be used for mapping with higher accuracy.…”
Section: Collection Of Landsat Data and Image Compositementioning
confidence: 99%
“…In recent years, GEE has been widely used for global-scale applications such as characterizing global forest cover change; forest expansion, loss, and gain from 2000 using large collections of Landsat scenes [5]; and crop yield estimation [21,22]. Other studies have also confirmed the ease of integrating various sources of temporal satellite imagery data and automating image classification routines for vegetation and land cover mapping using the GEE [17,[21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation